La parola che significa-ed-è: riflessioni sulla natura intransitiva del linguaggio poetico (Mantichora. Italian Journal of Performance Studies, 2020)
The aim of the paper is to reflect on the ‘auto-referential’ (or ‘auto-telic’) character of the poetical language. But the paradigma of an absolute auto-referentiality of the word finds its best illustration in the so-called «sacred languages»: the paper examines in particular the case of Psalm 119, as an impressive example of a text whose referential «content» (the divine Law) coincides at all with the text itself. In more philosophical terms, the linguistic intention of the biblical text implies the radical identity of language and reality: as Plato suggests in the core level of his Cratylus.